Respuesta :

Answer:

x = -b ± √b²-4ac /2a

a = 5

b= -6

c= 1

x = -(-6) ± √(-6)² - 4(5)(1) /2(5)

x = 6 ± √36 - 20 / 10

x = 6 ± √16 /10

x = 6 ± 4/10

Breaking into respective signs

x = 6 + 4/10 or 6 - 4/10

x = 10/10 or 2/10

x = 1 or 1/5

x = 1 or 1/5.

Answer:

1/5 and 1

Brainliest, please!

Step-by-step explanation:

5x^2 - 6x + 1 = 0

a = 5, b = -6, c = 1

(-b +-sqrt(b^2 - 4ac))/2a

(-(-6) +-sqrt((-6)^2 - 4(5)(1))/2(5)

(6 +- sqrt(16)/10

(6 +- sqrt(16))/10

(6 +- 4)/10

2/10 and 10/10

1/5 and 1